A Model of Atlantic Heat Content and Sea Level Change in Response to Thermohaline Forcing - Zhai, X; Johnson, H; Marshall, D (2011)
The response of ocean heat content in the Atlantic to variability in the meridional overturning circulation (MOC) at high latitudes is investigated using a reduced-gravity model and the Massachusetts Institute of Technology (MIT) general circulationmodel (MITgcm). Consistent with theoretical predictions, the zonal-mean heat content anomalies are confined to lowlatitudeswhen the high-latitude MOC changes rapidly, but extends to mid- and high latitudes when the high-latitude MOC varies on decadal or multidecadal time scales. This low-passfiltering effect of the mid- and high latitudes on zonal-mean heat content anomalies, termed here the "Rossby buffer," is shown to be associated with the ratio of Rossby wave basin-crossing time to the forcing period at high northern latitudes. Experiments using the MITgcm also reveal the importance of advective spreading of cold water in the deep ocean, which is absent in the reduced-gravity model. Implications for monitoring ocean heat content and sea level changes are discussed in the context of both models. It is found that observing global sea level variability and sea level rise using tide gauges can substantially overestimate the global-mean values. © 2011 American Meteorological Society.